2011
DOI: 10.7763/ijssh.2011.v1.16
|View full text |Cite
|
Sign up to set email alerts
|

Conflict in Human Capital Relationships: the Impact of Job Satisfaction on Job Involvement in a Workplace

Abstract: The labour-management relationship is often referred to as a natural adversary relationship, a disconnect, grounded in conflict. This study therefore examined the contribution of staff job satisfaction to their level of job involvement in a private institution. This study adopted a survey research design. One hundred and fifty (150) participants randomly selected completed the psychological tests. Multiple regression was used to analyse the data collected. The result showed that job satisfaction and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Some researchers [17,18,19,20] in previous studies show that relationship exist between transformational leadership style and work outcomes such as performance. Other researchers [21,22,23,24,25,26,27,28] found that employee engagement has positive significant relationship and influence on job performance. Levinson [24] Cleland et al [25] indicates that employees who are engaged would likely stay with their current organisation with increased performance.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 1 more Smart Citation
“…Some researchers [17,18,19,20] in previous studies show that relationship exist between transformational leadership style and work outcomes such as performance. Other researchers [21,22,23,24,25,26,27,28] found that employee engagement has positive significant relationship and influence on job performance. Levinson [24] Cleland et al [25] indicates that employees who are engaged would likely stay with their current organisation with increased performance.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…It is the concern of organisations to manage their employees to achieve maximum performance knowing that engaged employees outperform their disengaged colleagues. However, categories of disengaged employees and not engaged employees outnumber engaged employees both in Nigeria and other workforce [28,29]. Disengaged employees may pull back and distance themselves from their jobs emotionally and cognitively, meanwhile their performance suffers [30].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The simple random sampling was used in this study for collecting data. The items on the questionnaire were adapted, adopted and modified through readings of related literature and scales (Akinbobola, 2011;Kanungo, 1982;Kirwan & Birchall, 2006). The data from the questionnaire was analyzed through the use of Structural Equation Model-Partial Least Square (Smart-PLS) to test the formulated research hypotheses and analyze the collected data.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this evaluative behaviour, individuals identify themselves with the group and view themselves in relation to the values held or promoted by the group (Lee et al, 2014). In the current pandemic situation, comparable elements of rewards and pay may cause feelings of injustice and reduced satisfaction among employees, which may lead to employees becoming less involved in their job (Akinbobola, 2011). However, justice perception and embeddedness can be addressed with greater enmeshment, links and associations at work among people (Mallol et al, 2007), subsequently, improving the work-related quality of life (Haghgui, 2015).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%